The Association Between Self-Managed versus Clinician-Managed Abortion and Self-Reported Abortion Complications: A Cross-Sectional Analysis in India - Goemans S; Singh A; Yadav AK; McDougal L; Raj A; Averbach SH (Dove Medical Press, 2023)
Sophie Goemans,1 Abhishek Singh,2,3 Ajit Kumar Yadav,4 Lotus McDougal,5 Anita Raj,5 Sarah H Averbach1,5 1Department of Obstetrics, Gynecology, and Reproductive Sciences, University of California San Diego, La Jolla, CA, USA; 2Department of Public Health & Mortality Studies, International Institute for Population Sciences, Mumbai, Maharashtra, India; 3Centre of Demography of Gender, International Institute for Population Sciences, Mumbai, Maharashtra, India; 4GENDER Project, International Institute for Population Sciences, Mumbai, Maharashtra, India; 5Center on Gender Equity and Health, University of California San Diego, La Jolla, CA, USACorrespondence: Sarah H Averbach, Department of Obstetrics, Gynecology, and Reproductive Sciences, University of California San Diego, 9300 Campus Point Drive, San Diego, CA, MC 7433, USA, Tel +1 858-249-1205, Fax +1 858-657-7212, Email saverbach@health.ucsd.eduPurpose: To examine the association between self-managed abortion and the self-reported experience of abortion complications in India, a country with a high incidence of self-managed abortion.Patients and Methods: The study used a cross-sectional multivariable logistic regression analysis of data from the National Family Health Survey (NFHS-4) of 2015- 2016 to compare the odds of self-reported complications experienced during abortion between self-managed and clinician-managed abortions in India.Results: On average, self-managed abortions occurred earlier in gestation than clinician-managed abortions, 7.8 weeks and 11.3 weeks, respectively (p < 0.001). Self-managed abortion was associated with fewer self-reported abortion-related complications than clinician-managed abortions when adjusted for covariates not including gestational age (Adjusted Odds Ratio (aOR) 0.82, 95% confidence interval (CI) 0.69, 0.97). However, once adjusted for gestational age, there was no longer a clinically meaningful or statistically significant difference in the odds of self-reported complications between self-managed and clinician-managed abortions (aOR = 0.98, 95% CI 0.81, 1.18).Conclusion: These findings suggest that people in India are using safe methods to self-manage abortions and support the hypothesis that self-managed abortion can improve access to abortion and reproductive choice without increasing risk.Keywords: reproductive autonomy, reproductive choice, self-use, medication abortion, misoprostol, mifepristone